Improving Electrical Power Grid of Jordan and Control the Voltage of Wind Turbines Using Smart Grid Techniques - Nadeem T. Ahmad (Institute of Advanced Engineering and Science, 2013)
In this paper, we improved the national grid of Jordan country by adding a renewable resources specifically a wind turbines generation unites distributed on different places in Jordan to compensate the losses of the power in Jordan and to dispense with using the generation of fuel and gas by representing the national grid of Jordan in ETAB simulator and we solved the voltage problems of wind turbines using a new mythology using smart grid techniques